Prevalence, Severity, and Impact of Painful Diabetic Peripheral Neuropathy in Type 2 Diabetes - Davies, Mark; Brophy, Sinead; Williams, Rhys; Taylor, Ann (Diabetes care, 2006)
OBJECTIVE:--To determine the prevalence of painful diabetic peripheral neuropathy (PDPN) in a population-based sample and to estimate its severity and impact. RESEARCH DESIGN AND METHODS--A cross-sectional descriptive study consisting of two phases: phase 1, a postal survey to patients with type 2 diabetes (an initial screening questionnaire including one question about pain); phase 2, neurological history and examination using the Toronto Clinical Scoring System. Subjects with PDPN or mixed (PDPN and nonneuropathic) pain completed the Neuropathic Pain Scale and Neuroqol to assess severity and nature of the pain and impact on quality of life. Those without PDPN completed the Neuroqol only. RESULTS:--In phase 1, there was a 92.7% response (n = 326), with 208 (63.8%) subjects reporting pain. In phase 2, 269 (82.5%) subjects attended and 51 (19.0%) were found to have PDPN: 99 (36.8%) nonneuropathic pain, 20 (7.4%) mixed pain, and 99 (36.8%) no pain (PDPN prevalence 26.4%). Of those with PDPN, 80% stated that their pain was moderate or severe. Those affected had poorer quality of life than those with no pain (difference in mean scores 3.6 [95% CI 2.5-4.6%]) compared with those with nonneuropathic pain (1.7 [0.4-2.9%]). Both pain and neuropathy score were independently associated with quality of life, and subjects with PDPN had significantly higher neuropathy scores. CONCLUSIONS:--Our study showed a prevalence of PDPN of 26.4%. Having PDPN has a significant negative effect on quality of life, and increasing neuropathy is associated with an increasing risk of developing PDPN.